The warped sea of sailing: Maritime topographies of space and time for the Bronze Age eastern Mediterranean. (March 2019) - Safadi, Crystal; Sturt, Fraser
Abstract: Time has consistently been regarded as the missing dimension from our renderings of space, having a significant impact on how we interpret and represent past interaction. Nowhere is this more keenly felt than in discussion of maritime mobility. This paper outlines an innovative approach to mapping maritime spaces by taking into account the performance of Bronze Age sailing ships in different weather conditions and the subsequent time of sailing journeys. The use of cartograms is demonstrated to be invaluable for reconceptualisation of maritime space and rethinking maritime connectivity in the past. This marks a step-change in approach, which has implications for regions beyond the case study area (eastern Mediterranean). The results presented in this paper foreground meaningful differences in maritime connectivity between Egypt and the Levant during the earlier Bronze Age than are easily realised through traditional static representations. This demonstrates the significance of developing alternative representations of space/time for archaeology. Graphical abstract: Image 1 Highlights: Mediation with mapping for maritime spaces. Modelling the maritime space-time of ancient sailing by accounting for environmental rhythms and vessel performance. Distorting space according to time with linear cartograms. Rethinking maritime connectivity.